Patient‐specific finite element analysis of carotid artery stenting: a focus on vessel modeling. (29th September 2012) - Auricchio, F.; Conti, M.; Ferrara, A.; Morganti, S.; Reali, A.
SUMMARY Finite element analysis is nowadays a well‐assessed technique to investigate the impact of stenting on vessel wall and, given the rapid progression of both medical imaging techniques and computational methods, the challenge of using the simulation of carotid artery stenting as procedure planning tool to support the clinical practice can be approached. Within this context, the present study investigates the impact of carotid stent apposition on carotid artery anatomy by means of patient‐specific finite element analysis. In particular, we focus on the influence of the vessel constitutive model on the prediction of carotid artery wall tensional state of lumen gain and of vessel straightening. For this purpose, we consider, for a given stent design and CA anatomy, two constitutive models for the CA wall, that is, a hyperelastic isotropic versus a fiber‐reinforced hyperelastic anisotropic model. Despite both models producing similar patterns with respect to stress distribution, the anisotropic model predicts a higher vessel straightening and a more evident discontinuity of the lumen area near the stent ends as observed in the clinical practice. Although still affected by several simplifications, the present study can be considered as further step toward a realistic simulation of carotid artery stenting.Copyright © 2012 John Wiley & Sons, Ltd.